2020
DOI: 10.3390/w12030836
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Characteristics of Groundwater and Dominant Water–Rock Interactions in the Delingha Area, Qaidam Basin, Northwest China

Abstract: Groundwater is undoubtedly important for water supplies and eco-environment protection, especially for arid and semi-arid regions. Analyzing the characteristics and evolution of groundwater is significant for the rational management of groundwater resources. This study investigated the hydrogeochemical characteristics and evolutions of groundwater in the Delingha area, northeast of the Qaidam Basin, northwest China, with a total of 123 water samples, including 105 unconfined groundwater samples, 12 confined gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 20 publications
2
59
0
1
Order By: Relevance
“…The relation between Na and Cl − may indicate (i) halite dissolution if the Na/Cl − ratio is approximately 1; (ii) silicate weathering or cation exchange if the Na/Cl − ratio > 1, and (iii) an anthropogenic input if the Na/Cl − < 1 [8,58]. Figure 3a showed that most of the studied karst waters were along the 1:1 line or above, indicating that halite dissolution and silicate weathering were the most important sources of Na.…”
Section: Main Hydrochemical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between Na and Cl − may indicate (i) halite dissolution if the Na/Cl − ratio is approximately 1; (ii) silicate weathering or cation exchange if the Na/Cl − ratio > 1, and (iii) an anthropogenic input if the Na/Cl − < 1 [8,58]. Figure 3a showed that most of the studied karst waters were along the 1:1 line or above, indicating that halite dissolution and silicate weathering were the most important sources of Na.…”
Section: Main Hydrochemical Processesmentioning
confidence: 99%
“…The flow system is interrelated by joints, conduits and cavities, which influence its ability to deposit and transport water from the surface to the springs [7]. Due to the high heterogeneity of the aquifer and to the rapid flow velocities of water in a karst environment, pollutants can easily reach the groundwater and alter its quality [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Cl − showed positive correlation for SO 4 2− in groundwater. The strong positive correlations among water quality parameters exposed the weathering of carbonate rocks, evaporites, soil salts, and interaction of halite with groundwater as the common sources of increase in values of these ion in groundwater [45]. Other ions, NO 3 − and K + , did not have a strong correlation with other parameters.…”
Section: Statistical Verification Of Ions Co-occurrence and Sourcesmentioning
confidence: 87%
“…Anthropogenic influence on groundwater quality is described in Sections 3.4.1-3.4.3, representing high ionic concentrations in particular land use areas. Meanwhile, Gibbs diagrams provide basic information on natural factors that influence hydrogeochemical evolution [45]. The evolution starts from the Ca-HCO 3 water type because most of geology constituting aquifers contain silicate or carbonate minerals [46].…”
Section: Mechanism For Controlling the Hydrochemistry Of Groundwatermentioning
confidence: 99%
See 1 more Smart Citation